The effect of dietary fiber supplement on prevention of gestational diabetes mellitus in women with pre-pregnancy overweight/obesity: A randomized controlled trial - Zhang, Dong-Yao; Cheng, De-Cui; Cao, Yan-Nan; Su, Yao; Chen, Li; Liu, Wen-Yu; Yu, Yue-Xin; Xu, Xian-Ming (Frontiers in Pharmacology, 2022)
Objective: To investigate the association of dietary fiber intake during pregnancy with the prevention of GDM in pre-pregnancy overweight /obese pregnant women. Methods: This was a prospective, randomized controlled trial to evaluate the incidence of GDM. A total of 98 pre-pregnancy overweight/obese pregnant women (<20 weeks of gestation) were randomly assigned to the intervention group (20g dietary fiber/day) and the control group (standard prenatal care). Both groups received nutrition education and dietary advice during the study. Anthropometric indicators and body composition were measured at baseline and end of the trial. Comparisons were conducted using a χ2 test, Mann-Whitney U test, and t-test, respectively, between the measurement data and countable data of characteristics of the intervention and control group. GDM diagnosis was performed by an oral glucose tolerance test (OGTT) at 25-28 weeks’ gestation. Results: Incidence of GDM was significantly reduced in the intervention group compared with the control group: 8.3% vs. 24.0% (χ2 = 4.40, P < 0.036). At OGTT, the mean fasting plasma glucose in the intervention group was lower than before the intervention (4.57±0.38 vs. 4.41±0.29, P <0.01) compared with in the control group. The glucose intolerance was significantly better in the intervention than in the control group. The body weight gain was lower in the intervention group than in the control group (1.99±1.09kg vs. 2.53±1.20kg, P =0.022). Compared with the control group, the mean triglycerides were significantly higher in the intervention group (2.19±0.54 vs. 2.70±0.82, P =0.003). None of the women randomized to the intervention group occurred preterm birth compared with 12.0% in the control group (P = 0.040). Excessive weight gain occurred in 46.7% of women in the intervention group compared with 68.0% in the control group (P = 0.035). Apgar scores at 1min in the control group were significantly lower than for the intervention group (9.92±0.27 vs. 10±0.0, P = 0.044). There were no differences in other maternal and neonatal outcomes. Conclusion: Increasing dietary fiber intake in pregnant women with pre-pregnancy overweight/obesity may lower the risk of GDM, excessive weight gain, and preterm birth, but did not benefit blood lipids.